An Ayurvedic Approach in the Management of Female Infertility Caused due to Uterine Factor - Priyanka Kamble,; Swathi C,; L.V. Rathnakar, (International Journal of Ayurveda and Pharma Research, 2025)
Infertility due to multiple factors is one of the predominant health issues faced by married couples nowadays. It is common in 10-15% of couples. Both male and female factors contribute to the infertility. Ayurvedic approach is helpful in these steps to improve the overall health of the women. Shodhana therapy like Virechana and Basti work as the Garbha Adhana Shodhana procedure in the female and brings the Doshas in the Sama Avastha which will eventually help in conception. Materials and Methods: The case presented in the study is of a married couple who have been anxious to conceive for 9 years. She was started on Ayurvedic Shamana therapy to regularize her menstrual cycles last year. Later, she was admitted to the IPD for the Virechana and Yoga Basti procedure. Results: During the treatment, the patient regained regular menstrual cycles. She also has initiation of regular ovulation and has improvement in endometrial proliferation and layering. Conclusion: It is a case of infertility that includes multiple female factors such as uterine fibroids, uterine synechiae, irregular menstrual cycles, anovulation, and low AMH levels. Based on the parameters of Ayurvedic science this case was diagnosed as Vandhyatwa (infertility) The treatment included Shamana therapy to suppress the vitiated Vata and Kapha Dosha, and Shodhana to improve the Stroto Shuddhi for ovulation indication and adequate formation of endometrial layering. Hence, Ayurveda treatment can be used in patients with infertility with better outcomes.